2004
DOI: 10.1093/gerona/59.12.1295
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Thresholds for Reporting Mobility Disability Between National Population Subgroups and Studies

Abstract: There is evidence of differences in thresholds for reporting mobility disability, especially across age and income groups in older Americans. Further work is needed to understand the perceptual, attitudinal, or environmental factors that cause these reporting differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 14 publications
1
54
1
Order By: Relevance
“…First, we have used a self-reported measure of disability. However, two studies comparing self-reported function with observed performance found no gender differences in the reporting of disability [46,47] . Second, we chose to use a categorical measure of disability rather than a continuous measure of functional status.…”
Section: Discussionmentioning
confidence: 97%
“…First, we have used a self-reported measure of disability. However, two studies comparing self-reported function with observed performance found no gender differences in the reporting of disability [46,47] . Second, we chose to use a categorical measure of disability rather than a continuous measure of functional status.…”
Section: Discussionmentioning
confidence: 97%
“…30 Our findings are also consistent with results from NHANES III in the US indicating that higher income people may have more lenient standards for their health, reporting physical difficulties or inabilities only when they reach a more severe level of tested limitation. 21,36 In our analysis, this type of 'index shift' would correspond to the fact that a person with more education or higher income would have to be in worse health, as measured by mortality risk, in order to rate themselves in a lower SRH category compared with someone with less education or less income. ref.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Evidence of reporting heterogeneity for subjective health measures across SES groups within countries has been found in the UK, France, Canada, Israel and the US using a variety of benchmarks for 'objective' health. 9,13,[18][19][20][21] With respect to mortality, a number of recent studies have found significant race/ethnic and gender differences in the predictive effect of SRH in the US. [22][23][24][25] For instance, SRH is a weaker predictor of mortality for less-acculturated Hispanic adults, which some have suggested is due to a tendency to put a greater weight on non-life-threatening issues such as emotional and mental well-being in their health assessment, 22 though language and cultural differences in response styles are also plausible.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a longstanding debate within gerontology as to whether longer life is associated with a ''compression of morbidity'' (2), an ''expansion of morbidity'' (3,4), or a combination of both, with an increased prevalence of chronic diseases counterbalanced by a decrease in the severity and consequences of the same diseases (5). The evidence supporting these different perspectives is mixed, perhaps because of differences in research settings (e.g., cohorts, countries, and ethnicities) and methodology (e.g., response rates and assessment instruments) (6)(7)(8). Nonetheless, there are accumulating data that the prevalence of chronic disability is decreasing among the elderly (6,9).…”
mentioning
confidence: 99%